PELAKSANAAN FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH KOTA KUPANG TERHADAP KINERJA PEMERINTAH KOTA KUPANG DALAM BIDANG PENDIDIKAN DAN KESEHATAN - Kuhurima, Angelique Rosalia; Yohanes, Saryono; Ratu Udju, Hernimus (Petitum Law Journal, 2023)
The presence of the DPRD in a democratic country is not to reduce the authority of the executive but must be seen as an effort to better guarantee the interests of the people in all local government policies. DPRD in accordance with its nature as a legislative institution which has three main functions, namely the function of legislation, the function of the budget and the function of supervision. The Kupang City DPRD Secretariat formulates the Organizational Mission as the main task that must be carried out by the organization in order to achieve the Organization's Vision by taking into account the interests of all components and parties related to the organization. The reason is because a centralized party system makes DPRD members side with the party as a source of legitimacy rather than the voters and society. In addition, DPRD members often sort out areas of supervision. (1) How is the implementation of the supervisory function of the Regional People's Representative Council (DPRD) of the City of Kupang on the performance of the Kupang City government in the fields of education and health?(2) What are the inhibiting factors for the Regional People's Representative Council (DPRD) of the City of Kupang in carrying out the oversight function of the performance of the Kupang City government in the fields of education and health? This research is an empirical or sociological juridical legal research with the approach used in this research, namely: (1) Socio legal approach (2) Qualitative approach and then analyzed in a qualitative descriptive juridical manner.The results of this study indicate that: (1) The implementation of the supervisory function of the Regional Representatives Council of the City of Kupang has not been optimal as stated in the provisions of the applicable laws and regulations. (2) The inhibiting factors for the Kupang City Regional House of Representatives in carrying out their oversight function on the performance of the Kupang City government in the Education and Health sector are: Availability of Budget and the Covid-19 pandemic.